Pemberian ASI eksklusif dengan perkembangan bayi usia 6-9 bulan di kabupaten Labuhanbatu - Wahyuni Sujarwadi; Evawany Y Aritonang; Sri Rahayu Sanusi (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Exclusive breastfeeding with the development of 6 to 9 month - old babies in the Labuhanbatu RegencyPurpose: This study aims to analyze the relationship between the pattern of breastfeeding and exclusive breastfeeding with the development of infants aged 6-9 months in the work area of the Suka Makmur Health Center in Labuhanbatu Regency in 2018.Method: This type of research is analytical research with a cross-sectional study design. The population in this study were infants aged 6-9 months with a total sampling technique of 84 infants. The data analysis method used in this study was Chi-square analysis with a significance level of 95% (α = 0.05).Results: The results showed that 49 mothers (58.3%) gave exclusive breastfeeding. Chi-square analysis showed that there was a significant relationship between exclusive breastfeeding and the development of infants aged 6-9 months (p = 0,0001).Conclusion: There is a significant relationship between exclusive breastfeeding and infant development. Suggestions in this study were to increase motivation and encouragement from health workers to mothers to give breast milk exclusion to their babies for optimal infant development.